Potential role of circulating microRNAs as early markers of preeclampsia. - Ura, Blendi; Feriotto, Giordana; Monasta, Lorenzo; Bilel, Sabrine; Zweyer, Marina; Celeghini, Claudio (Taiwan J Obstet Gynecol, 2014)
OBJECTIVE: To identify microRNAs (miRNAs) differentially expressed at early stages of gestation (12-14 weeks) in the serum of pregnant women, who later developed severe preeclampsia (sPE) in the third trimester of pregnancy (n = 24) compared to women with normal pregnancy (n = 24). MATERIALS AND METHODS: Sera from 12-14-week-gestation whole blood were subjected to microarray analysis with TaqMan Low Density Array chips (human microRNA panel V3.0), and to quantitative real-time polymerase chain reaction. RESULTS: By using the TaqMan Low Density Array chip technology, 19 mature miRNAs appeared differentially expressed in the group of women who later developed sPE as compared to normal women. The expression of four miRNAs (miR-1233, miR-520, miR-210, miR-144) was validated by quantitative real-time polymerase chain reaction analysis. MiR-1233 was the most overexpressed in the serum of women who later developed sPE. CONCLUSION: Circulating miRNAs deserve further investigation in order to explore their potential role in the pathogenesis of preeclampsia. In particular, miR-1233 might represent a potential marker of early sPE.
Keywords: Adult; Biomarkers; Female; Gestational Age; Humans; MicroRNAs; Oligonucleotide Array Sequence Analysis; Pilot Projects; Pre-Eclampsia; Pregnancy; Retrospective Studies